Pengaruh Spaylater Dan Cod (Cash On Delivery) Terhadap Keputusan Pembelian Di Marketplace Shopee (Studi Pada Mahasiswa/i Universitas Muhammadiyah Kalianda) - Damayanti , Nita; Tamam, Tamam (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The use of the internet and mobile phones is not just to find various information, but people today make the internet, especially E-Commerce, part of their lifestyle. Shopee not only makes it easier to shop, but Shopee also makes it easy to make transactions when shopping. One of them is by payment methods using digital money such as ShopeePay, ShopeePay Later and COD. With ease in the purchase transaction process. This study was conducted to determine the influence of Shopeepay later and COD (Cash On Delivery) on the purchase decision of students of the University of Muhammadiyah Kalianda on the Shopee marketplace. In this study, the researcher used a quantitative research method and data was collected using a questionnaire. The sample taken amounted to 50 respondents using the purposive sampling technique. The instrument tests used are validation tests, reliability tests, classical assumption tests, quantitative analysis and hypothesis tests. The results of SPPSS 23 processing from the descriptive analysis can be concluded that the spaylater variable (X1) has a positive effect on the Purchase Decision variable (Y). The COD (Cash On Delivery) variable (X2) had no effect on the purchase decision (Y), then the spaylater variable (X1) and COD (X2) together had a positive effect on the purchase decision (Y).